2018
DOI: 10.1094/mpmi-12-17-0319-r
|View full text |Cite
|
Sign up to set email alerts
|

The Rust Fungus Melampsora larici-populina Expresses a Conserved Genetic Program and Distinct Sets of Secreted Protein Genes During Infection of Its Two Host Plants, Larch and Poplar

Abstract: Mechanisms required for broad-spectrum or specific host colonization of plant parasites are poorly understood. As a perfect illustration, heteroecious rust fungi require two alternate host plants to complete their life cycles. Melampsora larici-populina infects two taxonomically unrelated plants, larch, on which sexual reproduction is achieved, and poplar, on which clonal multiplication occurs, leading to severe epidemics in plantations. We applied deep RNA sequencing to three key developmental stages of M. la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Indeed, while the vast majority of the transcriptome was expressed during fungal colonization of both maize and soybean, the induction of genes underlying distinct, often divergent, biological processes were temporally distinct. This observation agrees with previous studies which identified temporal changes of gene expression during colonization of hosts by the same fungus exhibiting different lifestyles (Lahrmann et al, 2013;Lorrain et al, 2018), and this may suggest a reduction in a shift to necrotrophy on maize.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, while the vast majority of the transcriptome was expressed during fungal colonization of both maize and soybean, the induction of genes underlying distinct, often divergent, biological processes were temporally distinct. This observation agrees with previous studies which identified temporal changes of gene expression during colonization of hosts by the same fungus exhibiting different lifestyles (Lahrmann et al, 2013;Lorrain et al, 2018), and this may suggest a reduction in a shift to necrotrophy on maize.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of the rust fungi of the class Pucciniales, the hosts often belong to phylogenetically distant groups, such as angiosperms and gymnosperms or monocots and dicots (Aime et al ., ). The host switching within the life cycle in these cases is likely enabled by a strong separation of gene regulation in monokaryotic and dikaryotic hyphae (Lorrain et al ., ), which might be enabled by stage‐specific transcription factors that can only be activated or deactivated in the presence or absence of a second nucleus in a hyphal compartment. By switching hosts concomitantly, the possibility of variation beyond optimal interaction is provided – sub‐optimal performance on one of the two hosts may be outweighed by more successful performance on the other.…”
Section: Pathogens Maintain Effector Reservoirs That Are Crucial For mentioning
confidence: 99%
“…Very little information is available about infection mechanisms of alternate hosts and sexual stages. To date, only a handful of studies have considered gene expression on the alternate host and they have revealed concomitant expression of sets of candidate effectors in both hosts as well as in each host individually (Xu et al ., ; Liu et al ., ; Cuomo et al ., ; Lorrain et al ., ). This type of approach is particularly helpful for narrowing down the list of effectors related to the main host where disease causes the most significant damage.…”
Section: Rusts In the Genomics Era: The Ever‐expanding List Of Candidmentioning
confidence: 97%